Corrective Feedback in English Class for Adult Learners - Suzanna Widjajanti; Era Wahyu Ningsih (Faculty of Letters Universitas Balikpapan, 2023)
The focus of this study was corrective feedback by the tutor in correcting learners’ speaking performance in the Small Talk program that is held at PT United Tractors, Tbk Balikpapan collaborated with the Foreign Language Academy of Balikpapan for 3 months. This study identified occurrences of the correction of speaking performance learner errors including using proper grammar, pronunciation, vocabulary, and the way the tutor performed the corrective feedback. This study was descriptive qualitative research with participants numbered 15 learners and data were presented and analyzed inductively in terms of features and facts of the tutor’s teaching process. The result of the observation showed the tutor applied recast, elicitation, classification request, direct correction, metalinguistic, and repetition to respond to learners’ pronunciation, vocabulary, and grammatical errors during the learning process and based on the interview of two participants attended, they unanimously stated that in teaching and learning activities at the Small Talk Program, feedback is mostly needed in the form of corrections to errors made by participants